Is It Possible to Promote Egg Consumption During Pregnancy? Findings From a Study on Knowledge, Perceptions, and Practices in Kenya. Issue 2 (June 2019) - Schnefke, Courtney H.; Lutter, Chessa K.; Thuita, Faith; Webale, Albert; Flax, Valerie L.; Bentley, Margaret E.
Background: Eggs are nutrient rich and have the potential to improve maternal nutrition during pregnancy and birth outcomes, but cultural beliefs may inhibit consumption during pregnancy. Objective: To understand knowledge, attitudes, beliefs, practices, facilitators, and barriers related to consuming eggs during pregnancy in Kenya. Methods: The study had 3 phases. Phase I included in-depth interviews and free-listing and pile-sorting exercises with pregnant women (n = 36), husbands (n = 12), and mothers-in-law (n = 12) of pregnant women, and health providers (n = 24). Phase II involved egg preparation exercises with pregnant women (n = 39). Phase III involved a weeklong trial of egg consumption with pregnant women (n = 24). We used thematic content analysis methods to analyze qualitative data and tabulated quantitative data. Results: All participants recognized eggs as nutritious for pregnant women; 25% of pregnant women consumed eggs the previous day. However, participants believed eating too many eggs during pregnancy (1 or more eggs daily) leads to a large baby and delivery complications. Unaffordability and unavailability also inhibit consumption. Health workers are the most trusted source of information on maternal nutrition. Almost all women complied with the household trial, said they would continue eating eggs and would recommend eggs to other pregnant women in moderation. Conclusions: Although participants believed consuming eggs during pregnancy is beneficial, cultural norms, practices, and beliefs may prevent pregnant women from eating them daily. Interpersonal communication from health workers and agricultural policies to promote affordability could lead to increased consumption.